Study of hematological profile of systemic lupus erythematosus - Gulati, Shipra; Kumar, Vikas; Rawat, Preshika; Chawla, Kunal; Dessai, Rishikesh; Jain, Sunil (International Journal of Research in Medical Sciences, 2023)
Background: Hematological abnormalities are prevalent in systemic lupus erythematosus (SLE), with approximately 72% of patients experiencing anemia, primarily in the form of autoimmune hemolytic anemia. Other manifestations include leukopenia (32%), lymphopenia (54%), and thrombocytopenia (23%). This study aimed to further investigate these hematological manifestations, which may serve as presentations of SLE and might be overlooked if suspicion levels are low. Methods: A descriptive observational study was conducted over 18 months at a Sir Ganga Ram hospital, a tertiary care centre. One hundred thirteen SLE cases, comprising newly diagnosed patients and previously diagnosed patients’ records, were reviewed, with 13 cases excluded based on exclusion criteria. One hundred patients with hematological abnormalities and fulfilling ≥4 SLICC criteria for SLE diagnosis were included in the study. Results: One hundred cases of SLE with hematological abnormalities (88 women, 12 men) were analyzed. At presentation, 83% (n=84) of patients displayed hematological manifestations. The most prevalent abnormality was anemia, present in 72% of the study group, with a mean hemoglobin level of 10.073 gm/dl. Additionally, leukopenia, lymphopenia, thrombocytopenia, and pancytopenia were observed in 32%, 54%, 23%, and 14% of cases, respectively. Neutropenia was detected in only 5% of cases. Conclusions: Hematological manifestations are the most common presenting signs of SLE in North India. Anemia, with a multifactorial basis, is the most frequent hematological abnormality throughout the disease course. A high index of suspicion is crucial when evaluating cases of anemia in daily clinical practice.